Pengarusutamaan Gender dalam Program Pembangunan - Malau, Waston (Universitas Negeri Medan, 2014)
Many issues of gender inequality surrounding us still not yet seriously solved by all elements of society. Women have more experience in disadvantages rather than men in the fields of education, health, employment, having and using science and technology. As may be seen with the still frequently occur violence against women, trafficking of women and children, pornography, the employment of women as problems of migrant workers and migrant workers abroad, lower participation of women in politics, and in the field of education, especially at the senior high school and higher education. For solving that, efforts in eradicating gender discrimination and developing potency which can support gender equality must be conducted continuously. Despite Constitution of 1945 ensures equality between men and women in accessing the fields, but in application still faced by many obstacles, for instance culture of patriarchy still remained and perpetuated by most of Indonesian people. Therefore increasing the womenâs role in gender-based development as integral part of national development, has important meaning as effort to realize harmonious equal partnership between men and women, which in other word, to realize gender equity and equality in various fields of life and development.